Realigninng Economic Governance with Full Employment - Passaris, Constantine E. (HAPSc Policy Briefs Series, 2021)
Full employment remains an economic mirage and an elusive destination for most countries. The ascendance of the new global economy of the 21st century has revealed the economic governance fault lines and the need to redirect the scope and substance of economic policy. This has been accentuated by the cataclysmic trifecta of the first three decades of the 21st century. Human capital has emerged as the driver for the new economy in the creation of the wealth of nations. In effect, the paradigm for the creation of economic growth has shifted from the resources under our feet to the brain power between our ears. This policy brief concludes by proposing a new institution of economic governance whose overarching mandate is to achieve full employment.